1999
DOI: 10.1083/jcb.145.6.1309
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of the LAMA3 Gene in Mice Reveals Abnormalities in Survival and Late Stage Differentiation of Epithelial Cells

Abstract: Laminin 5 regulates anchorage and motility of epithelial cells through integrins α6β4 and α3β1, respectively. We used targeted disruption of the LAMA3 gene, which encodes the α3 subunit of laminin 5 and other isoforms, to examine developmental functions that are regulated by adhesion to the basement membrane (BM). In homozygous null animals, profound epithelial abnormalities were detected that resulted in neonatal lethality, consistent with removal of all α3-laminin isoforms from epithelial BMs. Alterations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
244
0
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(259 citation statements)
references
References 61 publications
8
244
0
4
Order By: Relevance
“…This mutation results in early embryonic lethality due to the failure of endoderm differentiation (50). In addition, it has been shown that the loss of lessubiquitous laminin subunit ␣5, ␣3, or ␤2 causes an intrinsically weaker BM, affecting different tissues (29,43,59). As nidogen-1-null and nidogen-2-null animals each on their own appear to develop normally without any evidence of structural alterations or deformity in the BM, we conclude that the lack of nidogen-1 or nidogen-2 has no effect upon laminin deposition.…”
Section: Discussionmentioning
confidence: 99%
“…This mutation results in early embryonic lethality due to the failure of endoderm differentiation (50). In addition, it has been shown that the loss of lessubiquitous laminin subunit ␣5, ␣3, or ␤2 causes an intrinsically weaker BM, affecting different tissues (29,43,59). As nidogen-1-null and nidogen-2-null animals each on their own appear to develop normally without any evidence of structural alterations or deformity in the BM, we conclude that the lack of nidogen-1 or nidogen-2 has no effect upon laminin deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted inactivation of hemidesmosome components in mouse shows that laminin-332 and a6b4-integrin are critical to construct stable hemidesmosomes (Table 2A) (Georges-Labouesse et al, 1996;van der Neut et al, 1996;Ryan et al, 1999;Meng et al, 2003). Their absence leads to severe skin blistering and near absence of hemidesmosomes, although reduced amounts of BP230, BP180, and plectin can still associate with the basal membrane.…”
Section: Initial Hemidesmosome Assemblymentioning
confidence: 99%
“…2C) Ryan et al, 1999;3 Dowling et al, 1996;4 Georges-Labouesse et al, 1996;5 Murgia et al, 1998;6 Raymond et al, 2005;7 van der Neut et al, 1996;8 Ackerl et al, 2007;9 Andra et al, 1997;10 Guo et al, 1995;11 Hresko et al, 1994;12 Ding et al, 2003;13 Ding et al, 2008;14 Hresko et al, 1999;15 Bosher et al, 2003. hemidesmosomes, the underlying mechanisms might be more complicated than the formation of vertebrate hemidesmosomes, which only happens on the basal side of the epidermis. The initial nucleation of hemidesmosomes might take place independently on either side of the epidermis.…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…(Costell et al, 1999) Tenascin C Extracellular matrix Total NC cells fail to disperse laterally (Tucker, 2001) Laminin γ1 Extracellular matrix Total Death at E5.5, lack of basement membranes (Smyth et al, 1999) Laminin β2 Extracellular matrix Total Postnatal death between P15-30, neuromuscular junctions and glomerular defects (Noakes et al, 1995a;Noakes et al, 1995b;Patton et al, 1997) Laminin α2 Extracellular matrix Total Death by 5 weeks postnatal, severe muscular dystrophy and peripheral neurophathy (Miyagoe et al, 1997) Laminin α2 (dy/dy) Extracellular matrix Spontaneous Adult lethality, severe muscular dystrophy and peripheral nerve dysmyelination (Patton et al, 1999;Patton et al, 1997) Laminin α3 Extracellular matrix Total Death at P2-3, epithelial adhesion defect (Ryan et al, 1999) Laminin α4 Extracellular matrix Total Transient microvascular defect with hemorrhages and misalignment of neuromuscular junctions (Patton et al, 2001;Thyboll et al, 2002) Laminin α5 Extracellular matrix Total Death at E14-E17, with placental vessel, neural (Miner et al, 1998;Miner and Li, 2000) Protein Function Type Phenotype Reference tube, limb, and kidney defects Fibronectin Extracellular matrix Total Death before E14.5, shortened anterior-posterior axes, deformed neural tubes, and defects in mesodermally derived tissues. (George et al, 1993) Collagen XVIII Extracellular matrix Total Eye abnormalities modeling Knoblock syndrome (Fukai et al, 2002) Extracellular matrix Total Basement membrane defects (Utriainen et al, 2004) Collagen XV Extracellular matrix Total Skeletal myopathy and cardiovascular defects (Eklund et al, 2001) betaglycan Extracellular matrix Total Embryonic lethality of heart and liver defects (Stenvers et al, 2003) Connexin 43 Cell-cell adhesion In vitro studies of cells from knockout mice…”
Section: Note On Nomenclaturementioning
confidence: 99%